DENV-Mimetic Polymersome Nanoparticles Bearing Multi-Epitope Lipopeptides Antigen as the Next-Generation Dengue Vaccine - Nur Adilah Abdul Rahman; Abdin Shakirin Mohamad Norpi; Muhammad Luqman Nordin; Mohd Cairul Iqbal Mohd Amin; Abdullah Al-Hadi Ahmad Fuaad; Nor Azila Muhammad Azami; Nirmal Marasini; Fazren Azmi (MDPI AG, 2022)
Dengue remains a severe threat to public health. The safety and efficacy of the licensed dengue vaccine is not clinically satisfactory, which necessitate the need of new approach in designing an effective dengue vaccine without eliciting adverse reaction. Herein, we have designed a lipidated multi-epitope peptide vaccine (LipoDV) that can elicit highly targeted humoral and cell-mediated immune responses. To improve its immunogenicity, LipoDV was presented on the surface of MPLA-functionalized polymersome nanoparticles (PNs-LipoDV-MPLA). The as-constructed vaccine delivery platform resembles the structural morphology of DENV owing to its spherical nanoscale particle size and surface immunostimulatory properties given by LipoDV and MPLA that emulating the functional role of DENV E and prM/M proteins respectively. A proof-of-concept study demonstrated that BALB/c mice immunized with PNs-LipoDV-MPLA induced a stronger antigen-specific antibody response with an enhanced cell-mediated immunity as characterized by the elevated IFN-γ secretion in comparison to other tested vaccine candidates which possess a lesser structural trait of DENV. The DENV-mimicking nanoparticles vaccine exhibited negligible toxicity as analyzed by hemolytic test, MTT assay, histopathological examination and abnormal toxicity test on immunized mice. Collectively, our study provides a strong foundation in designing an effective peptide-based vaccine delivery platform against DENV infection.